Pengaruh Green Product, Healthy Lifestyle, dan Brand Image Terhadap Keputusan Pembelian (Studi Pada Konsumen Produk Mie Lemonilo di Kota Denpasar) - Yuniari, Luh Putri; Rahanatha, Gede Bayu (Universitas Pahlawan Tuanku Tambusai, 2024)
Instant noodles are a product which answers the phenomenon of practical food in society. Companies must be able to innovate of their products to become consumers choices. In terms of instant noodle products themselves, companies that produces instant noodles, including Lemonilo, should be able to consider things that are factors in consumer purchase decisions by paying attention to phenomena or trends that exist in this era. There are several factors that influence purchase decisions, namely green product, healthy lifestyle, and brand image. This study aims to determine the effect of green product, healthy lifestyle, and brand image on purchase decision. The location of this research was in Denpasar City, with a sample of 100 respondents who were Lemonilo noodle consumers. The data collection technique used was a questionnaire. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis which includes classic assumption test, multiple linear regression analysis, hypothesis testing (t test), F test, and coefficient of determination test. Based on the research results, it is found that green product, healthy lifestyle, and brand image partially and simultaneously have a positive and significant effect on purchase decision. These results indicate that it is important to improve green products, pay attention to healthy lifestyles in society, and maintain brand image for companies in order to always be able to improve purchase decision.